3049 Prenatal care as a protective factor for preterm birth and smoking during pregnancy in nulliparous patients: a propensity score analysis - Alexandra Noel Houston-Ludlam; Alison G. Cahill; Kathleen K. Bucholz; Andrew C. Heath (Journal of Clinical and Translational Science, 2019)
OBJECTIVES/SPECIFIC AIMS: Preterm birth rates have been rising in the United States, and reducing preterm birth is a high-priority clinical and public health concern. There are no existing strategies to reduce preterm birth in nulliparous individuals. The present study aims to evaluate prenatal care as a protective factor for preterm birth in this population. METHODS/STUDY POPULATION: Missouri birth record data for child birth years 1993-2016 were used to create a sample of 325,088 singleton births to nulliparous women, themselves born in MO 1975-1985. Logistic regressions, stratified by maternal race (White, African-American, Asian, American Indian/Alaskan Native, Other), were used to predict preterm birth (< 37 weeks gestational age) as a function of 1) initiation of prenatal care of by end of first trimester and 2) Adequacy of Prenatal Care Utilization Index, with sociodemographic covariates of child birth year, maternal age, highest educational level, and marital status (four level variable, including married yes/no, and partner named on birth record, yes/no). Subsequent analyses will use this logistic regression to create a propensity score predicting smoking during pregnancy using birth record parental sociodemographic characteristics, stratified by maternal race. Primary analyses will focus on the role of prenatal care in predicting smoking during pregnancy and preterm birth risk within propensity score stratum. Secondary analyses will consider the role of other risk factors, including maternal pre-pregnancy BMI and maternal DUI history, on preterm birth risk. RESULTS/ANTICIPATED RESULTS: Preliminary logistic regressions predicting preterm birth were analyzed, stratified by maternal race. In White mothers, preterm birth prevalence was 8.2%, and risk was significantly increased by maternal age ≤ 15 and ≥ 31, being unmarried, and by receiving no prenatal care, yet unaffected by timing of prenatal care initiation. For African-American mothers, preterm birth prevalence was 11.9%, and risk was significantly increased by being unmarried and both by not initiating prenatal care by end of first trimester and receiving no prenatal care. Preliminary samples were too small for solid inferences for other races. Anticipated results are that after propensity score match, earlier initiation of prenatal care will show modest protective effect on preterm birth, but other characteristics such as maternal cigarette smoking during pregnancy and DUI status will show stronger effects on predicting preterm birth risk. DISCUSSION/SIGNIFICANCE OF IMPACT: By evaluating the role of prenatal care initiation and delivery on preterm birth, this work provides an evidence base for prenatal care schedules and for understanding the interplay of sociodemographics, healthcare delivery, and individual characteristics in the context of preterm birth risk and potentially reduce negative health outcomes.